Development of new hybrid ultrafiltration membranes by entanglement of macromolecular PPSU‐SO3H chains: Preparation, morphologies, mechanical strength, and fouling resistant properties. Issue 20 (4th February 2015) - Arumugham, Thanigaivelan; Kaleekkal, Noel Jacob; Doraiswamy, Mohan
ABSTRACT The present work focuses on the preparation of Polyphenylsulfone (PPSU) membranes with enhanced antifouling surfaces through an incorporation of sulfonated Polyphenylsulfone (PPSU‐SO3H), which acts as both, surface modifying agent and macromolecular additive. Initially, Sulfonated polyphenylsulfone (PPSU‐SO3H) was synthesized by using chlosulfonic acid via bulk modification method. The degree of sulfonation (DS, %) of PPSU‐SO3H was calculated by using NMR (nuclear magnetic resonance).The phase inversion technique was used to prepare all asymmetric membranes by allowing the PPSU‐SO3H (different wt %) to entangle with the PPSU membrane matrix. All prepared membranes were characterized by using scanning electron microscope (SEM), X‐ray diffraction analysis (XRD), contact angle analysis (CA), mechanical strength analysis, molecular weight cut off (MWCO), porosity (%), mean pore size, and BSA adsorption studies. The performance efficiency of the membranes was evaluated by using BSA protein as a model foulant in terms of permeability, rejection (SR %), Rm (hydraulic resistance), Rc (cake layer resistance), Rp (pore plugging resistance), Rr (reversible fouling), Rir (irreversible fouling), and FRR (flux recovery ratio). © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41986.